Longitudinal associations between personality traits and cognitive complaints in midlife and older age across 20 years - Aschwanden, Damaris; Allemand, Mathias; Kliegel, Matthias; Sutin, Angelina R.; Luchetti, Martina; Stephan, Yannick; Schilling, Oliver; Wahl, Hans-Werner; Olaru, Gabriel; Terracciano, Antonio (European journal of personality, 2025)
Cross-sectional work suggests that higher neuroticism and lower conscientiousness are consistently related to more subjective cognitive complaints. Little is known about the longitudinal associations. We used data from the Interdisciplinary Longitudinal Study of Adult Development to examine how personality and cognitive complaints jointly unfolded over 20 years. Participants came from a midlife (n = 502, Mage = 43.7) and an older age group (n = 500, Mage = 62.5). Random-intercept cross-lagged panel models were used to test the personality-complaint associations at the between-person and within-person levels. Analyses controlled for gender, education, subjective health, objective health, and memory. At the between-person level, higher neuroticism and lower conscientiousness were associated with more cognitive complaints over 20 years, and these associations were stronger in older than middle-aged adults. Among older adults, lower extraversion, openness, and agreeableness were longitudinally associated with more cognitive complaints. At the within-person level, all five traits were concurrently related to cognitive complaints, with small to medium-sized effects, but not across all measurement occasions. Few cross-lagged effects were found, with no consistent pattern across time or age cohorts. This work provides longitudinal evidence of personality-complaint associations and suggests that these associations varied more across individuals than within individuals over time.
Online verfügbar: 24. Oktober 2024
Gesehen am 02.07.2025